2008
DOI: 10.1111/j.1445-5994.2008.01649.x
|View full text |Cite
|
Sign up to set email alerts
|

Medications for the secondary prevention of ischaemic heart disease and heart failure are underutilized in dialysis patients

Abstract: The process for development of these consensus Australasian antifungal guidelines for use in adult patients with haematological malignancy is described. New features included, how the guidelines should be applied, the risk assessment tool used and the grading system for evidence and strength of recommendation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“… 10 Although there is a strong consensus that HiDAC regimen is a risk factor for IFI, and antifungal prophylaxis is warranted and recommended by clinical guidelines, using antifungal prophylaxis after HiDAC as consolidation treatment for AML in remission remains controversial. 11 14 More recently, a retrospective analysis in 27 patients receiving 76 cycles of HiDAC demonstrated that HiDAC as consolidation therapy was associated with low-risk of fungal infection and the incidence of documented IFI, empirical intravenous antifungal use and duration of antibiotic use were not increased. 15 …”
Section: Introductionmentioning
confidence: 99%
“… 10 Although there is a strong consensus that HiDAC regimen is a risk factor for IFI, and antifungal prophylaxis is warranted and recommended by clinical guidelines, using antifungal prophylaxis after HiDAC as consolidation treatment for AML in remission remains controversial. 11 14 More recently, a retrospective analysis in 27 patients receiving 76 cycles of HiDAC demonstrated that HiDAC as consolidation therapy was associated with low-risk of fungal infection and the incidence of documented IFI, empirical intravenous antifungal use and duration of antibiotic use were not increased. 15 …”
Section: Introductionmentioning
confidence: 99%
“…3 In patients deemed at high risk of IFD without an approved indication, antifungal prophylaxis was used at the discretion of the treating clinician in consultation with the infectious diseases department. In patients suspected of having an IFD because of clinical symptoms or persistent fever, the diagnostic work-up typically included imaging with high-resolution computed tomography (CT) of the chest and sinuses (if symptoms) or fluorine-18 fluorodeoxyglucose positron emission tomography/CT (FDG-PET/CT), followed by directed tissue sampling for microscopy and fungal culture.…”
mentioning
confidence: 99%
“…6 Within this schema, those ranked at highest risk of IFD include matched unrelated or mismatched allograft recipients, umbilical cord donor graft recipients, allogeneic HSCT recipients on immunosuppression for acute grade 2-4 or chronic extensive GVHD, and patients with acute myeloid leukaemia (AML) receiving cytarabine-based chemotherapy regimens for remission induction or re-induction. 7 Those AML patients receiving intensive consolidation treatment were also considered at high risk for IFD.…”
Section: Discussionmentioning
confidence: 99%